Design And Simulation of Dual-Purpose Solar Continuous Adsorption System Using Malaysian Activated Carbon - Alghoul, Mohammad Ahmed (2005)
Solar adsorption refrigeration is mainly realized using activated carbon as adsorbent and methanol as adsorbate. The study tested adsorption characteristics of three types of Malaysian activated carbons (AC-4060, AC-5060, AC-6070) with methanol by fitting Dubinin equation to the characteristic curve of the activated carbons and thus determine the available porosity. The P-T - X chart (pressure, temperature, and concentration) for each of the activated carbons was developed and the heat of adsorption was determined. A performance comparison of the activated carbons with methanol as the refrigerant for ice making was analyzed and the possibility of using the Malaysian activated carbon as adsorbent for adsorption refrigeration system was found satisfactory.For solar intermittent adsorption system, refrigeration process takes place at night. The use of the two adsorber beds working out of phase helps maintain a continuous refrigeration cycle. Efforts have been made to commercialize the single-purpose solar adsorption refrigeration system, but has not been well received. The dual-purpose solar continuous adsorption system for domestic refrigeration and hot water is the result of a series of researches done in the field of single-purpose of solar adsorption system for refrigeration with respect to the practical needs of industries and customers. A novel design and performance of a dual-purpose solar continuous adsorption system for domestic refrigeration and hot water is described. The system comprises of evacuated tube collectors, a water storage tank of two partitions each partition contains adsorber bed and condenser heat exchanger, a receiver, an evaporator, and ice box. Further more, the heat rejected by the adsorber beds and condensers during cooling process of refrigeration subsystem was recovered and used to heat water for the purpose of domestic consumption. In a continuous 24-hour cycle, 16.86 MJIday of heat can be recovered for heating of water storage tanks. In the single-purpose intermittent solar adsorption system, this heat is wasted. The total energy input to the dual-purpose system during 24-hour operation was 61.2 MJIday and the total energy output was 50 MJIday . The latter was made up of 44.69 MJIday for water heating and 5.3 MJIday for ice making. The amount of ice that can be produced was 12 kg lday.Based on typical values for the efficiency ( q ) of evacuated tube collector of water heating system of 65%, the following Coefficients of Performance COP'S were obtained: 44% for adsorption refrigeration cycle, 73% for dual-purpose solar water heater, 8.5% for dual-purpose solar adsorption refrigeration and 81.5% for dualpurpose of both solar water heater and refrigerator.